2018
DOI: 10.1155/2018/9718316
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Outcomes of Pregnant Women Who Have Had Invasive Prenatal Testing for the Prenatal Diagnosis of Duchenne Muscular Dystrophy

Abstract: Aim To show the importance of prenatal diagnosis of Duchenne Muscular Dystrophy (DMD) and to demonstrate the effect of DMD gene mutations on gestational outcomes. Materials and Methods We retrospectively evaluated 89 pregnancies in 81 individuals who were referred to Hacettepe University for prenatal diagnosis of DMD between January 2000 and December 2015. Prenatal diagnostic methods (chorionic villus sampling (CVS): 66, amniocentesis (AC): 23) were compared for test results, demographic features, and obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…21 These findings are not congruent with the study done in Turkey. 22 The majority of them (80%) reported no prior stillbirth, which is similar to the study done in Denmark. 23 Only 16.67% respondents reported that they had one stillbirth which is lower than that reported by Mikamo et al 4 In this study, 6.7% reported that they had one prior pregnancy loss while 5% reported that they had ≥ 2 prior pregnancy losses which are lesser than the findings in Netherlands.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…21 These findings are not congruent with the study done in Turkey. 22 The majority of them (80%) reported no prior stillbirth, which is similar to the study done in Denmark. 23 Only 16.67% respondents reported that they had one stillbirth which is lower than that reported by Mikamo et al 4 In this study, 6.7% reported that they had one prior pregnancy loss while 5% reported that they had ≥ 2 prior pregnancy losses which are lesser than the findings in Netherlands.…”
Section: Discussionsupporting
confidence: 83%
“…In other studies, abnormal screening test results, previous history of an affected child and prior pregnancy loss(es)/stillbirths were the main reasons for referral. 1,4,22 Responding to the history of prior induced termination of pregnancy, 6.7% of respondents reported that they had one induced termination of pregnancy. Nearly one-third (33.3%) reported that the current pregnancy was unplanned which is similar to the study done by Tsai et al 20 Of the respondents, 16.67% reported a history of a previously affected child with genetic anomaly which is quite higher than the other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal results reassure parents that their baby will be unaffected. However, abnormal results gives the couple a difficult decision as whether to ter minate or continue the pregnancy and prepare for postnatal affected infant [26]. In addition, irrespective of the results, some pregnancies may miscarry following the procedures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%